Protective Effects of Dexmedetomidine Infusion on Genotoxic Potential of Isoflurane in Patients Undergoing Emergency Surgery - Sadaf Aroosa; Adeel Sattar; Aqeel Javeed; Muhammad Usman; Mian Abdul Hafeez; Mehmood Ahmad (International Journal of Clinical Practice)
Background. Isoflurane (ISO) has been extensively uses in general anesthesia and reported to cause deoxyribonucleic acid (DNA) damage in prolonged surgical procedures. Dexmedetomidine (DEX) is an adrenergic agonist and having antioxidant activity that may reduce the genotoxic potential (DNA damage) and oxidative stress induced by ISO in patients undergoing major neurosurgical procedures. Methods and Findings. Twenty-four patients of ASA (American Society of Anesthesiologists) classes I and II were randomly divided into two groups (n = 12). Group A patients received ISO, while group B patients received DEX infusion for maintenance of anesthesia. Venous blood samples were collected at different time intervals and used to evaluate the oxidative stress marker malondialdehyde (MDA) and endogenous antioxidants superoxide dismutases (SOD) and catalases (CAT). A single-cell gel electrophoresis (SCGE)-comet assay was used to investigate the genotoxic potential of ISO. Conclusion. Increased level of antioxidants and decreased value of MDA and genetic damage index were seen in group B (P<0.001) in a time-dependent manner. Genetic damage was highest at point T2 (0.77 vs. 1.37), and continued to decrease till T3 (0.42 vs. 1.19), with respect to negative controls or baseline values following DEX infusion. Significantly, higher level of MDA was recorded in serum of group A (P<0.001) as compared to group B (1.60 ± 0.33 vs. 0.03 ± 0.001). Enzymatic activities of CAT and SOD were significantly higher in group B than group A (10.11 ± 2.18 vs. 5.71 ± 0.33), (1.04 ± 0.05 vs. 0.95 ± 0.01), respectively. It may play a contributing role in daily anesthesia practice and improve the toxic effects on patients as well as anesthesia personnel. Trial Registration. Ethical Committee of Post Graduate Medical Institute (PGMI), Lahore General Hospital approved the use of humans in this study vide human subject application number ANS-6466 dated February 04, 2019. Furthermore, as the clinical trials required registration from an appropriate registry approved by World Health Organization (WHO), this trail also retrospectively registered at Thai Clinical Trials Registry (an approved WHO registry for clinical trials registration) under reference ID TCTR20211230001 on December 30, 2021.